DEXMEDETOMIDINE VERSUS MAGNESIUM SULFATE FOR BLUNTING CARDIOVASCULAR RESPONSE TO LARYNGOS COPY AND ENDOTRACHEAL INTUBATION IN GENERAL ANAESTHESIA. - Dr. Richa Patel; Dr. Vijeta Tandel; Dr. Ushma Shah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Direct laryngoscopy and endotracheal intubation frequently induce cardiovascular stress response in form of tachycardia and hypertension due to reflex sympathetic stimulation which in turn leads to increased plasma norepinephrine concentration. Numerous drugs like opioids, calcium channel blockers, alpha2 agonists, magnesium sulphate, local anesthetics used to blunt the stress response. Magnesium sulphate, as the physiological calcium antagonist for membrane calcium channels can modify many calcium mediated response. The ability of Mg2+ ions to inhibit the release of catecholamines from both the adrenal glands and peripheral adrenergic nerve terminals has been known and is now well established. Dexmedetomidine is an alpha2 agonist stimulate alpha2 receptor in lateral reticular nucleus result in reduce central sympathetic outflow and blunting hemodynamics response to unpleasant stimulation. Pretreatment with dexmedetomidine provides sedation and analgesia also reduces sympathetic tone and attenuate the stress response to anesthesia and surgery.